2015
DOI: 10.1002/anie.201505237
|View full text |Cite
|
Sign up to set email alerts
|

Propane σ‐Complexes on PdO(101): Spectroscopic Evidence of the Selective Coordination and Activation of Primary CH Bonds

Abstract: Achieving selective C-H bond cleavage is critical for developing catalytic processes that transform small alkanes to value-added products. The present study clarifies the molecular-level origin for an exceptionally strong preference for propane to dissociate on the crystalline PdO(101) surface via primary C-H bond cleavage. Using reflection absorption infrared spectroscopy (RAIRS) and density functional theory (DFT) calculations, we show that adsorbed propane σ-complexes preferentially adopt geometries on PdO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Surprisingly, we found that dissociation of only one water molecule on (101) PdO is energetically unfavourable (Fig. 6) compared to undissociated water molecule, which is in agreement with pioneering studies by Weaver and co-workers [25][26][27][28][29][30][31][32]. The dissociated state is higher by 11 kJ/mol-Pd than the undissociated one.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Surprisingly, we found that dissociation of only one water molecule on (101) PdO is energetically unfavourable (Fig. 6) compared to undissociated water molecule, which is in agreement with pioneering studies by Weaver and co-workers [25][26][27][28][29][30][31][32]. The dissociated state is higher by 11 kJ/mol-Pd than the undissociated one.…”
supporting
confidence: 91%
“…It was determined that some optimal (not too small, >10 nm) size of PdO nanoparticles is required to effectively catalyze methane and hydrocarbon combustion in the studies by Chin and co-workers [21][22][23][24]. Moreover, XPS and DFT single-crystal studies of Weaver and co-workers [24][25][26][27][28][29][30][31][32] unambiguously identified that PdO (101) facet, containing coordinatively unsaturated tri-coordinate Pd(II)1O3 sites, is critical in inducing catalytic activity for both alkane and methane combustion. These particular tri-coordinate Pd(II) sites are able to form a σ-complex with methane: formation of such a complex creates a pre-requisite site with close geometric proximity between CH4 and PdO required for further heterolytic activation of methane C-H bond on the Pd-O pair, the latter representing the rate-determining step of methane combustion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are considerably shorter than for d 6 -propane weakly bound to an open Fe site in the MOF Fe 2 (dobdc) (∼3 Å), as analyzed by powder neutron diffraction at 4 K. 41 The 1,3-motif is similar to that proposed for propane coordination to a PdO(101) surface, albeit spanning two Pd sites. 45 The propane σ-complex Mn(η 5 -C 5 H 5 )(CO) 2 (propane) has been characterized in solution using in situ NMR spectroscopy at low temperature (133 K). 16 Given the quality of the refinement, hydrogen atoms were not located, and so the hapticity of the Rh···H–C interaction in [1-propane][BAr F 4 ] (e.g., η 1 or η 2 ) was interrogated using computational techniques ( section 2.3 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 A and B). It is well-known from pioneering studies of Weaver [38][39][40][41][42][43] and co-workers that for Pd catalysts to be active for methane and hydrocarbon oxidation, coordinatively unsaturated tri-coordinate sites on (101) planes of PdO nanoparticles should be present or, alternatively, contiguous coordinatively unsaturated sites on Pd metal surface. Thus, it is generally accepted in the literature and further validated in the combined theory-experimental studies of Chin, Iglesia and others [45][46][47] that nanoparticles of PdO of certain size exposing most reactive (101) facets are most active for methane combustion.…”
mentioning
confidence: 99%